MANFAAT RETALIASI SEBAGAI BAGIAN DARI RESOLUSI KONFLIK PERDAGANGAN DALAM SISTEM WTO BAGI INDONESIA - RM Muhammad Arridho Surya Putra (HI 15 UMY 466, 2015)
*466 The purpose of this study was to determine and analyze the constraints and obstacles faced by Indonesia as a developing country and a member of the WTO in using the instrument of conflict resolution retaliation. Then, this study aims to analyze the potential benefits to be gained when using retaliation Indonesia in the WTO system. Researchers will begin by describing an event study related law enforcement in the WTO system. Furthermore, we will look for what is becoming an obstacle for retaliation Indonesia to apply and what are the benefits that can be used Indonesia as a developing country when using the conflict resolution process retaliation in the WTO system. The experiment was conducted by using the method of the normative. All data were analyzed using qualitative methods. The results of this study are presented in a report that is descriptive analysis. This type of descriptive research that writers choose in writing this time, research will be carried out comparative approach and a case approach. Case approach would be to look at the case of conflict resolution facing Indonesia under the WTO system. The results show that constraints Indonesia to retaliation because of the political power of the state is opposed to Indonesian dispute, lack of human resources in Indonesia in conducting litigation in the WTO, Indonesia has economic interests conflict with opponents and different understanding among WTO member countries related to the strength binding rules of the WTO. Key Word: WTO, Retaliation, Conflict Resolution